Preparation of metal‐organic frameworks and their derivatives for supercapacitors. Issue 3 (15th August 2022) - Li, Youjian; Gan, Donglin; Deng, Xu; Jiang, Lili; Xie, Chaoming; Lu, Xiong
Abstract: To satisfy the requirements of social power development, it is urgently necessary to develop innovative and sustainable new energy storage devices. Supercapacitors have attracted considerable attention as a new type of energy storage device, owing to their high energy density, high power density, fast charging and discharging speeds, and long cycle life. The electrode material is an important factor in determining the electrochemical performance of supercapacitors. In recent years, researchers explored the application of metal‐organic frameworks (MOFs) and their derivatives as electrode materials for supercapacitors. In this paper, the preparation of monometallic, bimetallic, and conductive MOFs, and their derivatives for application in supercapacitors are reviewed. In addition, challenges facing MOFs in the field of supercapacitors and their future development prospects are discussed.